FRI0203 Golimumab in biologic-naÏve patients with established rheumatoid arthritis (RA), psoriatic arthritis (PSA) or ankylosing spondylitis (AS) - subanalysis from the non-interventional evaluation go-nice. (15th June 2017) - Krüger, K; Burmester, GR; Wassenberg, S; Bohl-Bühler, M; Thomas, MH
Abstract : Background: Golimumab (GLM) has demonstrated efficacy and safety in several randomized clinical trials with biologic-naïve patients. However, data from effectiveness and patient-reported outcomes (PROs) parameters in daily clinical practice in Germany are still lacking Objectives: The aim of this subanalysis is to assess Golimumab on the effectiveness, and PROs in biologic-naïve patients with established RA, PsA or AS Methods: This is a subanalysis of the non-interventional, prospective, 24-month study GO-NICE. Biologic-naïve patients with established RA, PsA or AS starting with GLM 50mg SC once monthly in a real life setting in Germany. Endpoint measures: disease activity DAS28, PsARC and BASDAI. PROs included QoL (EQ-5D-3L), functionality (FFbH), fatigue (FACIT-F). Safety data were also collected Results: RA patients (n=265): Mean age 54.5 yr, 82.1% of the patients were female, 77.3% (n=204) were rheumatoid factor (RF) positive, and 76.4% (n=201) had anti-ccp antibodies at BL. The DAS28 score at BL was 5.0 and dropped significantly to 2.9 within 24 months (p<0.0001 v. BL). After 3 months of treatment, 45.2% of patients had LDA (DAS28 ≤3.2), which increased to 50.8% after 6 month and 64.9% after 24 months. PsA patients (n=247): Mean age 49.7 yr, 53.8% of the patients were female, 42.1% (n=104) had a nail involvement, 25.5% (n=63) dactylitis and 13.8% (n=34) enthesitis at BL. The proportion of patients achieving a response (mod PsARC) was 64%, 72.2% and 77.7% at 3, 6 and 24 months, respectively. AS patients (n=246): Mean age 41.9 yr, 70.7% of the patients were male, 80.5% (n=198) were HLA-B27 positiv. Most common extraarticular manifestations were: enthesitis (12.6%), iritis (12.2%), IBD (3.7%), and dactylitis (2.8%) at BL. The BASDAI at BL was 5.0 and dropped significantly to 2.0 within 24 months (p<0.0001 vs. BL). The proportion of patients achieving a response (BASDAI 50) was 62.2%, 66.9% and 76.9% at 3, 6 and 24 months, respectively. An improvement of quality of life (QoL) by EQ-5D-3L was seen after 6 months and was maintained over 24 months. The patients' health state today (EQ VAS) improved from 52.3 at BL to 64.9 (RA), from 49.0 to 66.3 (PsA) and from 49.2 to 70.6 (AS). The functional ability (FFbH) improved significantly (p<0.0001 vs. BL) from 73.1 to 80.4 points (RA), from 73.0 to 82.2 (PsA) and from 72.8 to 81.2 (AS). The mean Fatigue score (FACIT-F) increased from BL: 33.3 to 39.5 points (RA), from 31.6 to 38.4 points (PsA), and from 31.6 to 40.2 points (AS) (each p<0.001 vs BL) within 24 months. No new safety signals were detected. Conclusions: GLM SC once-monthly showed after 3 months remarkable improvements in clinical effectiveness, patient-reported quality of life, functionality, and fatigue parameters and were maintained over 24 months in biologic-naive patients with established RA, PsA or AS. At month 24, 64.9% of RA patients achieved LDA status, 77.7% of PsA achieved positive PsARC response and 76.9% of AS patients achieved BASDAI 50. No new safety signals were detected. Disclosure of Interest: K. Krüger Consultant for: AbbVie, BMS, Celgene, Janssen Biologics, MSD, Pfizer, Roche, and Sanofi-Aventis, G. Burmester Consultant for: AbbVie, BMS, MSD, Pfizer, Roche, and UCB, S. Wassenberg Consultant for: AbbVie, Chugai, Janssen Biologics, MSD, Novartis, Pfizer, Roche, and UCB, M. Bohl-Bühler Consultant for: AbbVie, Hexal, MSD, Roche, and UCB, M. Thomas Employee of: MSD Sharp & Dohme GmbH Germany